Magneto-hydrodynamic simulations of young supernova remnants and their energy-conversion phase. Issue 1 (10th May 2021) - Petruk, O; Kuzyo, T; Orlando, S; Pohl, M; Brose, R
ABSTRACT: Supernova remnants (SNRs) can be rich sources of information on the parent SN (supernova) explosion. Thus, investigating the transition from the phase of SN to that of SNR can be crucial to link these two phases of evolution. Here, we aim to study the early development of SNR in more detail, paying the major attention to the transition from the early expansion stage to the Sedov stage and the role played by magnetic field in this transition. To this end, spherical magnetohydrodynamic simulations of SNRs have been performed to study the evolution of magnetic field in young SNRs and explore a sequence of the SNR evolutionary stages in the pre-radiative epoch. Remnants of three supernova types are considered, namely, SNIa, SNIc, and SNIIP, that covers a wide space of parameters relevant for SNRs. Changes in global characteristics and development of spatial distributions are analysed. It is shown that the radial component of magnetic field rapidly drops downstream of the forward shock. Therefore, the radially aligned polarization patterns observed in few young SNRs cannot be reproduced in the 1D MHD simulations. The period SNR takes for the transition from the earliest ejecta-driven phase to the Sedov phase is long enough, with its distinctive physical features, headed by the energy conversion from mostly kinetic one to a fixed ratio between the thermal and kinetic components. This transition worth to be distinguished as a phase in SNR evolutionary scheme. The updated sequence of stages in SNR evolution could be the free expansion (of gas) – energy conversion – Sedov–Taylor – post-adiabatic – radiative.